Sn vs. Ge: Effects of Elastic and Plastic Deformation of LGPS-type Solid Electrolytes on Charge-Discharge Properties of Composite Cathodes for All-solid-state Batteries - Kenta WATANABE; Hideaki NAKAYAMA; Han-Seul KIM; Kazuhiro HIKIMA; Naoki MATSUI; Kota SUZUKI; Satoshi OBOKATA; Hiroyuki MUTO; Atsunori MATSUDA; Ryoji KANNO; Masaaki HIRAYAMA (Electrochemistry)
The charge-discharge properties of all-solid-state batteries are affected by both chemical and physical factors. Physical issues mainly arise from the microstructure of the composites and the mechanical properties of the solid electrolytes themselves. However, physical issues have been investigated by focusing on the microstructures of the composites rather than the mechanical properties of the solid electrolytes themselves. In this study, composite cathodes with similar microstructures were fabricated using LiCoO2 as the active material and either Li9.81Sn0.81P2.19S12 or Li10GeP2S12 as the solid electrolyte. The composite with Li9.81Sn0.81P2.19S12 exhibited higher capacity retention and coulombic efficiency with increasing C-rates at 1.9–3.6 V vs. In-Li than that with Li10GeP2S12. Moreover, when charging–discharging at 1.9–3.8 V, where the expansion and shrinkage of LiCoO2 were greater those at 1.9–3.6 V, the composite with Li9.81Sn0.81P2.19S12 exhibited a higher capacity, capacity retention, and Coulombic efficiency than those of the composite with Li10GeP2S12. These results are attributed to the high elastic modulus, high yield stress, and volumetrically-large elastic-deformability, which enable Li9.81Sn0.81P2.19S12 to reversibly deform while maintaining contact with LiCoO2, unlike Li10GeP2S12. These results demonstrate that solid electrolytes with low elastic moduli are not absolutely suitable for all-solid-state batteries, and that a high yield stress and volumetrically-large elastic-deformability are especially significant for reversible deformation. These findings provide new insights for the development of composite electrodes for all-solid-state batteries.